A Critical Analysis of Commercial Frauds in the International Supply Chain with Available Remedies in Pakistan - Shan Ali; Waqas Irshad; Faheem Raza Khuhro (Journal of Management Practices, Humanities and Social Sciences, 2022)
Due to the result of globalization, international trade and supply chains have rapidly been witnessed across the borders, which has forced the law makers and jurists to develop legal framework for the issues arising out of fraud involved in transaction of supply and chain. However, World Trade Organization (WTO) has been playing a dominant role in policing the issue of commercial fraud in the supply chain by providing guidelines and mechanism to the member states for the enactment within the national laws. Consequently, Pakistan as a developing country has brought a number of legal reforms in its national legislation and has made attempts in tackling the issue as per the guidelines provided by WTO but such reforms have proved to stillborn for its ineffectiveness in dealing with commercial fraud in the international supply chain. Therefore, this study highlights the disputes arising in the supply chain and explores the reasons for the ineffectiveness of existing mechanism to resolve these conflicts at the national level by critically analyzing existing laws in light of the International Trade Law (ITL) and IL. In this context, this study highlights the major issues and suggest factor which can be incorporated into existing laws. This study suggests that there should be a proper mechanism and legal framework which identify